Determinant Intention to Become Nazir: An Empirical Study to Improve the Waqf Ecosystem in Indonesia - Badawi, Badawi (Jurnal Ekuisci, 2024)
It is crucial to recognize the need for human resources to sustain Indonesia's waqf ecosystem as it develops in that country. This study aims to identify the factors that affect a person's decision to become a nazir. The theoretical underpinning for this study is the Theory of Planned Behavior (TPB). This study had 220 respondents from Cirebon, Indonesia. With the use of SmartPLS 3.0, structural equation modeling was used to examine the data for this investigation. The analysis results show that Attitude – Job Market Consideration significantly positively affects a person's intention to become Nazir. Subjective Norm also has a significant positive effect on intention. In addition, Perceived Behavioral Control – Technical Skills Self-Efficacy has a significant positive effect on a person's intention to become a Nazir.